Al-Qawā’id Al-Fiqhiyyah dalam Persepektif Hukum Islam - Said Aqil. H Al-Munawwar (Al-Jami'ah: Journal of Islamic Studies, 1998)
As can be seen from the title, this article is trying to disclose al-qawā'id al-fiqhiyyah (legal maxims) as a means to ease the process of legal finding in Islamic law. By using both linguistic and legal approaches, Muslim jurists, at the outset were trying to build certain legal thinking framework which can be used as a basis for creating law for new cases whose solution cannot be found directly in the primary sources of Islamic law. It is here that those legal foundations then being developed as legal maxims used commonly by all disciples of each school of law. Although the Sunnī jurists are not unanimous concerning the role of qawā'id al-fiqhiyyah as a source of law, they all seem to realize the importance of the maxim in giving the solution toward many new legal problems arose in everyday life. Thus, we see that all four schools of Islamic law accepted the legal maxims as an argument in the process of law-making, especially in the new cases left unanswered by Qur'ān and Sunnah.